2020
DOI: 10.1002/biot.201900424
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Functional Metal‐Organic Frameworks in Biosensors

Abstract: In recent decades, fast advancements in the fields of metal‐organic frameworks (MOFs) are providing unprecedented opportunities for the development of novel functional MOFs for various biosensing applications. Exciting progress is achieved due to the combination of MOFs with various functional components, which introduces novel structures and new features to the MOFs‐based biosensing applications, such as higher stability, higher sensitivity, higher flexibility, and higher specificity. This review aims to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 100 publications
0
42
0
Order By: Relevance
“…In addition, MOFs, a kind of functional material exhibiting large specific surface areas and pore size distributions, multiple active sites, and clipping structures, were usually used as precursors to prepare metal phosphides 36‐38 . MOF‐derived nickel phosphide (Ni 2 P) was prepared via a simple, cost‐effective procedure using inexpensive and abundant elements 39 .…”
Section: Preparation Of Metal Phosphidesmentioning
confidence: 99%
“…In addition, MOFs, a kind of functional material exhibiting large specific surface areas and pore size distributions, multiple active sites, and clipping structures, were usually used as precursors to prepare metal phosphides 36‐38 . MOF‐derived nickel phosphide (Ni 2 P) was prepared via a simple, cost‐effective procedure using inexpensive and abundant elements 39 .…”
Section: Preparation Of Metal Phosphidesmentioning
confidence: 99%
“…Cancer cell capture, detection and release were achieved in a much different manner by Ou et al [ 77 ], who reported a novel sandwich-type “cytosensor” based on a DNA tetrahedron-linked dual-aptamer (reminiscent of that described in section 4.2 ) and a metal organic framework (MOF), which is a broad class of compounds consisting of metal ions or metal clusters coordinated with organic ligands to form one-, two-, or three-dimensional structures that are often porous. Applications of functional MOFs in biosensors have been reviewed in 2020 by Du et al [ 78 ]. In the present instance, the tetrahedron DNA nanostructures comprised of linked aptamers to both AS1411 (section 2 .)…”
Section: Cell Capturementioning
confidence: 99%
“…However, enzymes immobilized onto MOFs via physical adsorption tend to show low operational stability. In addition, due to the disordered arrangement of the enzymes on the surface of the material, enzyme desorption may take place [101]. Figure 6, below, shows the schematic representation of this immobilization process.…”
Section: Surface Attachmentmentioning
confidence: 99%
“…As glucose is the primary energy source in cells, it also plays a vital role in the growth of tumors [105]. Thus, blocking the availability of this sugar in tumor cells can be a good alternative for treating tumors [101]. MOF-based biomimetic nanoreactors (TGZ @ eM) were developed and coupled to GOx, and the prodrug tirapazamine (TPZ) was encapsulated in the porous regions of MOFs [106].…”
Section: Glucose Oxidase-integrated Mofs As Biosensorsmentioning
confidence: 99%